Lumberjanes. 8, Stone cold - Watters, Shannon; Leyh, Kat (Lumberjanes, 2018)
The Lumberjanes rush over to the Zodiac Cabin, excited that Barney is finally at the camp with them--but instead they find everyone in Zodiac turned to stone. April, Jo, Molly, Mal, and Ripley have to find a cure without looking the wrong thing in the eye and turning to stone in themselves.